2013
DOI: 10.1021/nn401420h
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Band Gap Photoluminescence from Atomically Thin Transition-Metal Dichalcogenide Alloys

Abstract: Band gap engineering of atomically thin two-dimensional (2D) materials is the key to their applications in nanoelectronics, optoelectronics, and photonics. Here, for the first time, we demonstrate that in the 2D system, by alloying two materials with different band gaps (MoS2 and WS2), tunable band gap can be obtained in the 2D alloys (Mo(1-x)W(x)S(2) monolayers, x = 0-1). Atomic-resolution scanning transmission electron microscopy has revealed random arrangement of Mo and W atoms in the Mo(1-x)W(x)S(2) monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

55
662
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(722 citation statements)
references
References 51 publications
55
662
4
1
Order By: Relevance
“…Although the differences in the Raman spectra for Nb and Mo doping were small, we observed significant changes in the PL spectra for Nb-doped samples, which has never been observed for Mo doping in monolayer WS 2 . 15,24,28) As seen in Fig. 3(a), undoped WS 2 monolayers have a PL peak at 1.98 eV, and the peak originates from the emission of free neutral and charged excitons.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Although the differences in the Raman spectra for Nb and Mo doping were small, we observed significant changes in the PL spectra for Nb-doped samples, which has never been observed for Mo doping in monolayer WS 2 . 15,24,28) As seen in Fig. 3(a), undoped WS 2 monolayers have a PL peak at 1.98 eV, and the peak originates from the emission of free neutral and charged excitons.…”
mentioning
confidence: 92%
“…As an impurity, Mo atoms are well studied and cause bandgap narrowing through the substitution of W sites in monolayer WS 2 . 14,15,23,24) However, there are very few studies on the doping of other transition metals for monolayer TMDCs. In the present study, Nb is selected because its atomic size is comparable to that of Mo and it is reported to generate acceptor states for some TMDCs.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Depending on the arrangement of its S atoms, monolayer MoS 2 appears in many distinct phases, two of them are more popular and exhibits substantially different electronic structures: 2H (trigonal prismatic, D 3h ) MoS 2 is a semiconductor with a finite band gap between the filled d z 2 and empty d x 2 − d y 2 ,xy bands, and 1T (octahedral geometry, O h ) phase is metallic with Fermi level lying in the middle of degenerate d xy,yz,xz single band. 9 It has been recently demonstrated that the reversible transition from 2H to 1 T phase can be achieved in monolayer MoS 2 by annealing, 10 electric doping, 11,12 applying strain 13 or electron-beam irradiating.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) characterization of the Mo (1-x) W x S 2 monolayer alloys has shown the continuously tuned emission from 1.82 eV (reached at x ¼ 0.20) to 1.99 eV (reached at x ¼ 1). 8,9 Moreover, centimeter-scale and highquality Mo 0.5 W 0.5 Se 2 alloy films were obtained on both a rigid SiO 2 /Si substrate and a flexible polyimide (PI) substrate. 10 For the second type of alloy, two different chalcogen atoms present in the alloy [MoS 2(1-x) Se 2x (Refs.…”
mentioning
confidence: 99%